2013
DOI: 10.1179/1467010013z.000000000137
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implantation in asymmetrical hearing loss for children: Our experience

Abstract: Cochlear implantation in children with an asymmetrical hearing loss is now becoming more recognized as an appropriate and beneficial treatment option. In our programme, we have been implanting children with asymmetrical hearing loss since 2008. Asymmetrical hearing loss is defined as hearing loss when one ear meets criteria for cochlear implantation and the other ear has better hearing and receives benefit from a hearing aid. There is a wide range of asymmetrical hearing loss: single-sided deafness is the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…Results from CI surgery in young children with acquired SSD suggest results comparable to those of adults suffering from acquired SSD [Cadieux et al, 2013;Hassepass et al, 2013;Plontke et al, 2013;Tzifa and Hanvey, 2013;Távora-Vieirea and Rajan, 2015]. Evidence of rehabilitation of binaural hearing skills in quiet and noise as well as improvement in the localisation of sounds has been demonstrated.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Results from CI surgery in young children with acquired SSD suggest results comparable to those of adults suffering from acquired SSD [Cadieux et al, 2013;Hassepass et al, 2013;Plontke et al, 2013;Tzifa and Hanvey, 2013;Távora-Vieirea and Rajan, 2015]. Evidence of rehabilitation of binaural hearing skills in quiet and noise as well as improvement in the localisation of sounds has been demonstrated.…”
Section: Introductionmentioning
confidence: 82%
“…Evidence of rehabilitation of binaural hearing skills in quiet and noise as well as improvement in the localisation of sounds has been demonstrated. Moreover, CI surgery remains the only treatment option available to individuals with SSD that may enable children to regain or improve binaural hearing [Arndt et al, 2011b;Cadieux et al, 2013;Gordon et al, 2013;Plontke et al, 2013;Tzifa and Hanvey, 2013]. Hassepass et al [2013] reported improvements in speech comprehension in noise and localisation of sound following CI surgery in 3 children with unilateral hearing loss (UHL).…”
Section: Introductionmentioning
confidence: 99%
“…In children with asymmetric hearing loss, Cadieux et al report significant CNC and BKB-SIN speech improvements when children listened bimodally versus CI-only or HA-only conditions [37]. Concordant with Cadieux, Tzifa and Hanvey report improvements in CAPII (7/7) and SIR (6/8) scores in children with asymmetric hearing loss utilizing an implant [38].…”
Section: Speech Benefits After Unilateral Cochlear Implantationmentioning
confidence: 93%
“…As such, children with SSD should be implanted-ideally as soon as possible because the best outcomes in SSD children have been associated with early implantation [38]. Many children with SSD demonstrate delays in speech and language comprehension [41,42] as well as an increased likelihood of academic difficulty [2 •• , 43].…”
Section: Unilateral Cochlear Implant Candidacymentioning
confidence: 99%
See 1 more Smart Citation